PEMANFAATAN TUMBUHAN PADA MASYARAKAT KASEPUHAN DESA CISUNGSANG DIKAWASAN TAMAN NASIONAL GUNUNG HALIMUN KABUPATEN LEBAK BANTEN - Wardah Wardah (Research Center for Biology-Indonesian Institute of Sciences, 2005)
Kasepuhan ethnic group surrounding Mt. Halimun National Park uses plants traditionally. Based on our research in May 2004 in Cisungsang, Lebak District, Banten province, there are 113 species of plants belongs to 41 families used in many ways. There are 20 local rice varieties, 30 species as vegetables, 30 species as medicinal properties, 28 species as food, 2 species as ornamental plants, 2 species as handycraff and 1 species as for dye. The wisdom in the traditional knowledge of this ethnic group is be discussed.